2017
DOI: 10.2147/ppa.s132751
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren’s syndrome is associated with negatively variable impacts on domains of health-related quality of life: evidence from Short Form 36 questionnaire and a meta-analysis

Abstract: PurposeThe purpose of this article was to systematically review the literature to identify the impact of primary Sjögren’s syndrome (pSS) on specific health-related quality of life (HRQoL) domains.MethodsA meta-analysis was performed, and the related articles were searched in Medline, Embase, Cochrane Library, China National Knowledge Infrastructure, China Biology Medicine, and Web of Science databases and in reference lists of articles and systematic reviews. Score of the Short Form 36 (SF-36) questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…The non-SS group had the lowest scores in all eight dimensions of the SF-36. Several earlier studies have previously demonstrated that patients with pSS have lower GHRQoL than healthy controls [55][56][57][58] . There are studies that have investigated QoL in patients with other systemic disorders such as rheumatoid arthritis (RA) 36 and systemic lupus erythematosus 59,60 .…”
Section: General Health-related Quality Of Life Patients With Medicamentioning
confidence: 98%
“…The non-SS group had the lowest scores in all eight dimensions of the SF-36. Several earlier studies have previously demonstrated that patients with pSS have lower GHRQoL than healthy controls [55][56][57][58] . There are studies that have investigated QoL in patients with other systemic disorders such as rheumatoid arthritis (RA) 36 and systemic lupus erythematosus 59,60 .…”
Section: General Health-related Quality Of Life Patients With Medicamentioning
confidence: 98%
“…Sjögren's syndrome (SS) is a chronic autoimmune disease in which the exocrine glands are the main tissue damaged, especially salivary and lacrimal glands. As one of most common autoimmune diseases, SS affects 0.5% to 1.0% of the population and is most commonly observed in women in the fifth decade of life . SS can present as primary Sjögren's syndrome (pSS) or secondary Sjögren's syndrome (sSS) according to whether the patient has another autoimmune disease .…”
Section: Introductionmentioning
confidence: 99%
“…As one of most common autoimmune diseases, SS affects 0.5% to 1.0% of the population and is most commonly observed in women in the fifth decade of life. 1 SS can present as primary Sj€ ogren's syndrome (pSS) or secondary Sj€ ogren's syndrome (sSS) according to whether the patient has another autoimmune disease. 2 Clinically, dryness is the overwhelming complaint, although other general features (fatigue and chronic pain) and extraglandular manifestations (including lymphoma) are also involved.…”
Section: Introductionmentioning
confidence: 99%
“…It affects predominantly the female sex and is characterized by lymphocytic infiltration of exocrine glands and other organs, resulting in dry eye and dry mouth and extraglandular systemic findings, such as pain, myalgia or polyarthralgia, among others [ 1 ]. The condition has a marked negative impact on health-related quality of life and social functioning [ 2 ].…”
Section: Introductionmentioning
confidence: 99%